The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1088/0963-0252/19/6/065016
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical determination of the efficiency of a sub-atmospheric flowing high power cascaded arc hydrogen plasma source

Abstract: Cascaded arc plasma sources with channel diameters between 4 and 8 mm were experimentally investigated at discharge currents up to 900 A and hydrogen (H 2 ) flow rates up to 10 slm. Pressure measurements at the arc exit showed that the heavy particle temperature in the discharge channel was about 0.8 eV. The electron temperature was calculated from the electron mass balance, taking into account electron losses due to ambipolar diffusion and convection out of the source channel. This calculation showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…It is found that the plasma flow inside the arc channel is compatible with the description of a laminar flow from Ref. 17. Accordingly, in Fig.…”
Section: Sealing Pressure Characteristicssupporting
confidence: 81%
See 2 more Smart Citations
“…It is found that the plasma flow inside the arc channel is compatible with the description of a laminar flow from Ref. 17. Accordingly, in Fig.…”
Section: Sealing Pressure Characteristicssupporting
confidence: 81%
“…The temperature decreases with the gas flow rate, while increases with the arc current, and these trends have a good agreement with Vijers's results. 17,18 As higher gas flow rate will lead to increase of inlet pressure, according to Ref. 27, electron temperature will decrease as increasing the pressure in the discharge channel.…”
Section: A Plasma Parameters Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the source manipulator water cooled cascaded arc sources [3] of different configurations can be installed depending on the requirements for plasma density and plasma temperature ranges. During plasma operation, the gas flows (up to 66.7 Pa m 3 /s per gas), gas types and cathode to anode current can be changed.…”
Section: Magnum-psi Installationmentioning
confidence: 99%
“…This is an unprecedented high value for a steady-state cascaded arc source and more than a factor of two higher than achieved in Pilot-PSI. 20 We attribute this high efficiency to low transport losses due to the low background pressure.…”
mentioning
confidence: 98%